An introduction to the Emergency Department Adult Clinical Escalation protocol: ED-ACE. Issue 9 (14th November 2016) - Coughlan, Eoin; Geary, Una; Wakai, Abel; O'Sullivan, Ronan; Browne, John; McAuliffe, Eilish; Ward, Marie; McDaid, Fiona; Deasy, Conor
Abstract : Purpose of the study: This study demonstrates how a participatory action research approach was used to address the challenge of the early and effective detection of the deteriorating patient in the ED setting. The approach enabled a systematic approach to patient monitoring and escalation of care to be developed to address the wide-ranging spectrum of undifferentiated presentations and the phases of ED care from triage to patient admission. This paper presents a longitudinal patient monitoring system, which aims to provide monitoring and escalation of care, where necessary, of adult patients from triage to admission to hospital in a manner that is feasible in the unique ED environment. Methods: An action research approach was taken to designing a longitudinal patient monitoring system appropriate for the ED. While the first draft protocol for post-triage monitoring and escalation was designed by a core research group, six clinical sites were included in iterative cycles of planning, action, reviewing and further planning. Reasons for refining the system at each site were collated and the protocol was adjusted accordingly before commencing the process at the next site. Results: The ED Adult Clinical Escalation longitudinal patient monitoring system (ED-ACE) evolved through iterative cycles of design and testing to include: (1) a monitoring chart for adult patients; (2) a standardised approach to the monitoring and reassessment of patients after triage until they are assessed by a clinician; (3) the ISBAR (I=Identify, S=Situation, B=Background, A=Assessment, R=Recommendation) tool for interprofessional communication relating to clinical escalation; (4) a template for prescribing a patient-specific monitoring plan to be used by treating clinicians to guide patient monitoring from the time the patient is assessed until when they leave the ED and (5) a protocol for clinical escalation prompted by single physiological triggers and clinical concern. Conclusions: This tool offers a link in the 'Chain of Prevention' between the Manchester Triage System and ward-based early warning scores taking account of the importance of standardisation, while being sufficiently adaptable for the unique working environment and patient population in the ED.